Synergy of Earth Observations with other smart, monitoring platforms (e.g. UAVs) for precision farming: The case of vineyards in Greece - Βλαχόπουλος, Οδυσσέας (Πανεπιστήμιο Πελοποννήσου, 2017)
The recent leaps in technological advancements and the capabilities for low cost and high quality equipment has provided the agricultural and scientific community with tools and analytical methodologies that enable rapid, easy and consistent data acquisition for farming purposes. Site-specific agricultural analysis has been performed for a pilot vineyard in the region of Attiki, Greece, during the important cultivation period of summer (June to August 2017) in regard to possible stress factors, irrigation issues, crop vigor, hydrological behavior etc., utilizing airborne and space-borne remote sensing techniques, while developing the zonal approach as a potent strategy to address those issues and consequently optimize the cultivation practices. The current study exercises precision agriculture for vineyards, otherwise called precision viticulture. The methodology and the instrumentation utilized have been chosen and engineered in regard to crops specific spectral reflectance and emissivity characteristics, employing an Unmanned Aircraft Systems (UAS) with thermal and multispectral monitoring capabilities. A commercial four-band and panchromatic sensor array, the Parrot SEQUOIA multispectral sensor and the radiometric Flir Vue Pro R thermal camera comprised the remote sensing UAS payloads, performing flights over the ~20ha vineyard area. The specific pilot site has been due to its high internal variability . The multispectral, panchromatic and thermal datasets were processed through a photogrammetric pipeline to create orthomosaics of the surveyed area. These orthomaps were employed to extract Vegetation Indices like the Normalized Difference Vegetation Index (NDVI), the Red Edge Chlorophyll Index (CI-RedEdge) and others. The pilot vineyard is also examined for the temporal variation of its several characteristics through the open Sentinel-2 satellite images, atmospherically corrected, in order to provide a holistic and consistent approach to the remotely sensed vineyards. The whole procedure has been labored through the open Geographic Information System platform QGIS utilizing where needed Python and R programming languages and the commercial Pix4D software. The UAS orthomosaic products and the satellite multispectral images of the vineyard were assessed for their information capacity and PV contemporary value. The overall results were highly rich in their information qualities and quantities, highlighting the spatiotemporal variation within the vineyard and providing indications for stress evaluation and optimization strategies through the interpretation of the grapevines specific characteristics, while illustrating the potential of advanced techniques like hyperspectral monitoring, very high resolution satellite imaging and the inseparable in situ components.
Συνέργεια των παρατηρήσεων της γης με άλλες έξυπνες πλατφόρμες παρακολούθησης (π.χ. UAV) για καλλιέργεια ακριβείας: Η περίπτωση των αμπελώνων στην Ελλάδα
Μ.Δ.Ε. 83
Keywords: vineyard; unmanned aerial vehicle; UAV; unmanned aircraft system; UAS; precision farming; agriculture; viticulture; multispectral; thermal; photogrammetry; vegetation index; Sentinel 2; remote sensing; earth observation